Statistical mechanics of elasticity - Weiner, Jerome Harris, 1923- (Dover Publications, 2002)
Advanced, self-contained treatment illustrates general principles and elastic behavior of solids. Part 1, based on classical mechanics, studies thermoelastic behavior of crystalline and polymeric solids. Part 2, based on quantum mechanics, focuses on interatomic force laws, behavior of solids, and thermally activated processes. 96 figures. 1983 edition.